Are Consumers Always Greener on the Other Side of the Fence? Factors That Influence Green Purchase Intentions – The Context of Croatian and Swedish Consumers - Branka Dropulić; Zoran Krupka (Tržište, 2020)
Purpose – Seeking to understand sustainability through the concept of green marketing mix and green consumer behaviour better, this paper examines their role in expressing green purchase intentions. Aiming to get a better insight into green consumer behaviour, it explores two important psychographic and behavioural variables: environmental awareness and perceived consumer effectiveness. The concept of both marketing mix and green consumer behaviour are examined in two very different contexts (Croatia and Sweden). Design/Methodology/Approach – To conduct the research, a self-completed highly structured questionnaire was designed. Green product characteristics were defined through the concept of marketing mix, while green consumers were defined according to their demographics and two psychographic and behavioural variables. The research was conducted among Croatian and Swedish consumers. Findings and implications – The research showed that the two samples, despite differences, have two factors of influence on green purchase intention in common: perceived higher quality of green products and environmental awareness. Both Croatian and Swedish consumers showed willingness to pay the premium price for green products, which shows the important role of price as a quality communicator of green products. Eco-labels, once they become a standard as is the case of the Swedish market, no longer have strong influence on green purchase intention. Limitations – The main limitation of this research is the fact that only low involvement products were used in the questionnaire. Originality – The main contribution of the paper is a deeper insight in purchase intentions of green consumers. The factors that drive green purchase intentions are observed in two different cultural, political and economic contexts, which adds value to green consumer understanding, but also contributes to better understanding of green product management.